Vitamin C enhances vitamin E status and reduces oxidative stress indicators in sea bass larvae fed high DHA microdiets - Betancor Quintana, Mónica Beatriz; Caballero Cansino, María José; Terova, Genciana; Corà, Samuela; Mohamed Ibrahim Azam, Reda Saleh; Benítez Santana, Tibiábin; Bell, J. Gordon; Hernández Cruz, Carmen María; Izquierdo López, María Soledad (Lipids, 2012)
Docosahexaenoic acid (DHA) is an essential fatty acid necessary for many biochemical, cellular and physiological functions in fish. However, high dietary levels of DHA increase free radical injury in sea bass (Dicentrarchus labrax) larvae muscle, even when vitamin E (alpha-tocopherol, alpha-TOH) is increased. Therefore, the inclusion of other nutrients with complementary antioxidant functions, such as vitamin C (ascorbic acid, vitC), could further contribute to prevent these lesions. The objective of the present study was to determine the effect of vitC inclusion (3,600 mg/kg) in high DHA (5 % DW) and alpha-TOH (3,000 mg/kg) microdiets (diets 5/3,000 and 5/3,000 + vitC) in comparison to a control diet (1 % DHA DW and 1,500 mg/kg of alpha-TOH; diet 1/1,500) on sea bass larvae growth, survival, whole body biochemical composition and thiobarbituric acid reactive substances (TBARS) content, muscle morphology, skeletal deformities and antioxidant enzymes, insulin-like growth factors (IGFs) and myosin expression (MyHC). Larvae fed diet 1/1,500 showed the best performance in terms of total length, incidence of muscular lesions and ossification degree. IGFs gene expression was elevated in 5/3,000 diet larvae, suggesting an increased muscle mitogenesis that was confirmed by the increase in the mRNA copies of MyHC. vitC effectively controlled oxidative damages in muscle, increased alpha-TOH larval contents and reduced TBARS content and the occurrence of skull deformities. The results of the present study showed the antioxidant synergism between vitamins E and C when high contents of DHA are included in sea bass larvae diets. 1207 1193 0,888 2,557 Q2 Q2 SCIE